Evaluasi implementasi program makan bergizi gratis (mbg) di sekolah dasar x kota bandar lampung - Muhammad Rizal Habib; Lindia Gemesu Pratiwi; Hardiansyah Hardiansyah; Undang Rosidin; Handoko Handoko (Universitas Sebelas Maret, 2025)
Abstract. The Free Nutritious Meals Program is a strategic effort by the government to improve the nutritional status of students while supporting the learning process in elementary schools. The success of the program is largely determined by the quality of its implementation at the school level. This study aims to evaluate the implementation of the Free Nutritious Meals Program at Elementary School X in Bandar Lampung City using the Context, Input, Process, and Product (CIPP) evaluation model. This study uses a qualitative approach with data collection techniques through observation and interviews with program managers, principals, teachers, students, and parents. The results of the study show that the program is highly relevant to the nutritional needs of students and has a positive impact on their enthusiasm for learning. However, there are still obstacles in the form of delays in fund disbursement, menus that do not match the schedule, and leftover food due to student preferences. In general, the program is running quite well, but it still needs to be strengthened in terms of educational assistance and periodic menu evaluation.Keywords: Free Nutritious Meals Program, CIPP Evaluation, Elementary School